Fungal root symbionts of high-altitude vascular plants in the Himalayas - Kotilínek, Milan; Hiiesalu, Inga; Košnar, Jiří; Šmilauerová, Marie; Šmilauer, Petr; Altman, Jan; Dvorský, Miroslav; Kopecký, Martin; Doležal, Jiří (Scientific reports, 2017)
Arbuscular mycorrhizal fungi (AMF) and dark septate endophytes (DSE) form symbiotic relationships with plants influencing their productivity, diversity and ecosystem functions. Only a few studies on these fungi, however, have been conducted in extreme elevations and none over 5500 m a.s.l., although vascular plants occur up to 6150 m a.s.l. in the Himalayas. We quantified AMF and DSE in roots of 62 plant species from contrasting habitats along an elevational gradient (3400-6150 m) in the Himalayas using a combination of optical microscopy and next generation sequencing. We linked AMF and DSE communities with host plant evolutionary history, ecological preferences (elevation and habitat type) and functional traits. We detected AMF in elevations up to 5800 m, indicating it is more constrained by extreme conditions than the host plants, which ascend up to 6150 m. In contrast, DSE were found across the entire gradient up to 6150 m. AMF diversity was unimodally related to elevation and positively related to the intensity of AMF colonization. Mid-elevation steppe and alpine plants hosted more diverse AMF communities than plants from deserts and the subnival zone. Our results bring novel insights to the abiotic and biotic filters structuring AMF and DSE communities in the Himalayas.
Keywords: Symbiosis; India; Endophytes; Mycorrhizae; Microscopy; Plant Roots; Indie; biodiverzita; mykorhiza; kořeny rostlin; symbióza; Altitude; fylogeneze; endofyty; mikroskopie; Phylogeny; nadmořská výška; Biodiversity